HEALTH STATUS OF SCHOOL CHILDREN OF POKHARA VALLEY, NEPAL - Lochana Shrestha; J B.K. Khattri (Journal of Nepal Medical Association, 2003)
ABSTRACT The cross sectional study to assess the health and nutritional status of school children in the age group of 4-15 years was carried out in 6 government primary schools of Pokhara valley by health team of the department of Social & Preventive Medicine (SPM), Manipal College of Medical Science, Pokhara, Nepal. A total of 750 students of both sexes, 368 boys and 382 girls were examined. The prevalence of wasting and stunting in these children were low (10.3% & 15.7% respectively) with boys suffering more than girls in both aspects. The 6-10 years old children were affected most. Pediculosis, Dental caries and Worm infestation were three most common diseases suffered by students. The study highlighted the need for continuation of school health services aimed at improvement of their health & nutritional status.